Lisp - Winston, Patrick; Horn, Berthold ([S.l.] : Addison-Wesley, 1993)
This third edition is a revised and expanded version of Winston and Horn's best-selling introduction to the Lisp programming language and to Lisp-based applications, many of which are possible as a result of advances in Artificial Intelligence technology. The Knowledge You Need The new edition retains the broad coverage of previous editions that has made this book popular both with beginners and with more advanced readers -- coverage ranging from the basics of the language to detailed examples showing Lisp in practice. Based on the CommonLisp standard, this book also introduces CommonLisp's object system, CLOS, and the productivity-promoting techniques enabled by object-oriented programming. Application examples drawn from expert systems, natural language interfaces, and symbolic mathematics are featured, and new applications dealing with probability bounds, project simulation, and visual object recognition are introduced. Special Features of this Edition *Based on extensive teaching experience *Explains key problem solving paradigms, such as search, forward chaining, and problem reduction *Discusses constraint propagation, backward chaining, and key ideas in Prolog *Emphasizes procedure and data abstraction, and other points of programming style and practice *Covers cliches, mapping, streams, delayed evaluation, and techniques for better and faster procedure definition 0201083191B04062001.